The Effect of Hydroxy-Beta-Methyl Butyrate Supplementation and Boxing Training on Oxidative Stress Indices in Male Boxers: A Randomized Clinical Trial - Mehd Fatahi; Farzaneh Taghian (Vesnu Publications, 2020)
Introduction: The production of free radicals during exercise is involved in the development of muscle damage and the development and spread of inflammation following exercise. Studies have confirmed the positive effect of Hydroxy-beta-Methyl Butyrate (HMB) in reducing oxidative stress indices.The purpose of this study is to compare the effect of HMB supplementation and boxing training on oxidative stress indices in male boxers.Materials and Methods: 40 male boxers were selected through convenience sampling and were randomly divided into 4 groups (10 participants per group) of boxing training, HMB supplementation, combination, and placebo. The participants in the boxing training group performed boxing exercises for eight weeks, 3 sessions per week every other day. At the same time, the participants in the HMB supplement group consumed 7 g HMB per each kilogram of body mass. The group refrained from boxing while studying. The combined group performed boxing exercises and took HMB supplements at the same time, and the control group performed boxing exercises and placebo. Blood samples were taken to measure malondialdehyde (MDA), superoxide dismutase, and carbonyl protein 24 hours before the first day of intervention and 24 hours after the last day of intervention. The data were analyzed using analysis of covariance (ANCOVA). P value less than 0.05 was considered significant.Results: The results showed that there was no significant difference between the effects of HMB supplementation, boxing training, and combination of HMB supplementation and boxing training on MDA in male boxers (P = 0.436). However, there was a significant difference between the effect of HMB supplementation, boxing training, and the combination of HMB supplementation and boxing training on the protein carbonyl (P = 0.02). The mean of protein carbonyl in the boxing athletes with supplement was significantly better than the other groups (P = 0.013).Conclusion: In general, due to the effectiveness of HMB supplementation and boxing training on some indicators of oxidative stress, supplementation with the appropriate dose is recommended to athletes.